Health education and prevention - Pizon, Frank (London : Wiley-ISTE, 2019)
Social representations, beliefs, values and knowledge are just some of the aspects that affect how the beneficiaries of preventative health measures perceive their wellbeing. Health Education and Prevention questions and analyzes these concepts in order to consider new ways of theorizing patients' conceptions of their health. From a methodological point of view, these analyses are put into practice with the design of prevention tools and devices. The use of a corpora of photographs is particularly meaningful in this respect. This book offers an authoritative perspective by noting important points of vigilance in training, and especially by distinguishing instructive contents conducive to the development of an explicit health pedagogy for more effective prevention measures. A model for categorizing situations integrating both educational and healthcare paths is also proposed.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed April 15, 2019).
Keywords: Health education; Electronic books; Electronic books